Trimetazidine and N-acetylcysteine in attenuating hind-limb ischemia and reperfusion injuries: Experimental study in rats - Da Silveira, M. [UNESP] (2009)
Aim. Lower-limb traumatic injury associated with ischemia and followed by reperfusion (I/R) is a common severe situation in muscle lesions due to trauma and hypoxia followed by local and systemic injuries induced by oxygen-derived free radical release during reperfusion. The aim of this study was to evaluate the attenuating effects of trimetazidine (TMZ) and N-acetylcysteine (NAC) in such situation. Methods. The muscles at the root of the right hind limb of Wistar rats were cross-sectioned, preserving femoral vessels and nerves and clamping the femoral artery for four hours. The clamp was then released and the femoral artery has been reperfused for 2 hours. Rats were randomly divided in groups of ten as follows: Group 1: sham I/R, treated with saline; Group 2: I/R, treated with saline; Group 3: sham I/R, treated with TMZ (7.5 mg/kg/dose); Group 4: sham I/R, treated with NAC (375 mg/kg/dose); Group 5: I/R treated with TMZ (7.5 mg/kg/dose); Group 6: I/R treated with NAC (375 mg/kg/dose). All rats received two intravenous bolus injections of the drugs, one before ischemia and one before reperfusion. Oxidative stress in plasma (MDA, total, oxidized and reduced glutathione), creatinephosphokinase (CPK), optical and electron microscopy and pelvic extremity circumference and volume were studied. Results. No statistical differences were found between the groups for MDA or total and reduced glutathione. Oxidized glutathione increased significantly in groups 5 and 2. Limb circumference as well as limb volume increased in all groups over time, mainly in groups 5, 2 and 1. CPK increased in all groups, being highest in groups 5, 6 and 2. Histological lesions were present in all but sham groups, being less severe in group 6. Soleus muscle analyses at electron microscopy exhibit some degree of alteration in all groups. Conclusion. This experimental model simulated severe limb trauma associated with ischemia and reperfusion, and, as such, it was aggressive, causing severe injury and local inflammatory reaction. The model did not show antioxidant action from NAC, and possible antioxidant action from TMZ was insufficient to attenuate tissue injuries.